Prediksi Jumlah Tamu Menginap di Hotel Karlita International, Tegal, Jawa Tengah - Haryadi Sarjono; Irwan Zulkifli (Binus Business Review, 2013)
Article is forecasting comparative analysis of number of guess room occupancy at Karlita International Hotel, Tegal, Central Java using 11 forecasting methods: linear regression, moving average, weighted moving average, exponential smoothing, exponential smoothing with trend, naïve method, trend analysis, additive decomposition – CMA, additive decomposition – average all, multiplicative decomposition – CMA, multiplicative decomposition – average All. Article used 17 data from January 2012 to Mei 2013, and results after using those 11 methods were the smallest MAD is 101.69 and the smallest MSE is 15,163.95. From additive decomposition – average all method, data showed guess room occupancy forecast at Karlita International Hotel for June 2013 is 960 guess.